Strategi Guru Akidah Akhlak Dalam Pembinaan Karakter Siswa Madrasah Aliyah DDI Hasanuddin Kabupaten Maros - Al Ghazali, Muhammad; Tahir, Ilyas; Sampurno, Bambang; Wahab, Abdul (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study examines the strategies of Akidah Akhlak teachers in character development of grade X students at Madrasah Aliyah DDI Hasanuddin, Maros Regency, including the forms of development, supporting factors, and inhibiting factors. The background of the study is based on the urgency of character education in forming students with noble character, especially through the Akidah Akhlak subject which emphasizes the internalization of moral and spiritual values. Using a qualitative approach with a case study design, this study collected data through participatory observation, semi-structured interviews, and document analysis. The results of the study indicate that the character development strategies implemented include habituation, role models, providing advice, discussing values, and reinforcement through religious activities such as tadarus and congregational prayer. Development is carried out comprehensively, both inside and outside the classroom. Supporting factors include a religious madrasah environment, the active role of teachers, and religious extracurricular activities, such as Rohis. Conversely, inhibiting factors include lack of parental supervision and negative influences from the external environment.